Atividades do (2E,3E)-3-buten-2-ona-4-(4-hidroxi-3- metoxifenil)-2-(4-(4-metoxifenil)-2-tiazolil)hidrazona, um análogo da curcumina, em modelos de dor e inflamação. - Sarah Olivia Alves Mendes da Costa (2020)
Modifications of the chemical structures of substances with therapeutic potential represent a promising alternative aiming drug development. Curcumin is a major polyphenol isolated from the rhizome of turmeric (Curcuma longa) and widely used in traditional medicine due to its therapeutic properties, mainly antiinflammatory. Due to curcumin low bioavailability, curcumin analogues have been synthesized in an attempt to improve in biopharmaceutical characteristics and increase the biological effects. In the present study, we investigated the activity of a curcumin analogue ((2E,3E)-3-buten-2-one-4-(4-hydroxy-3methoxyphenyl )-2-(4-(4-methoxyphenyl)-2-thiazolyl)hydrazone; RI75) in models of nociceptive, inflammatory and neuropathic pain and acute inflammation in mice. Previous intraperitoneal (i.p.) administration of RI75 (40 mg/kg) reduced the mechanical allodynia induced by carrageenan or paclitaxel. However, RI75 did not change the latency in the model of nociceptive response induced by heat. The animal motor activity was not altered by the administration of RI75. The antinociceptive activity of the RI75 was inhibited by previous administration of naltrexone (5 or 10 mg/kg, i.p.) or cyproheptadine (5 or 10 mg/kg, i.p.), but not glibenclamide (20 or 40 mg/kg, per os). Pretreatment with RI75 (20 or 40 mg/kg, i.p.) reduced paw edema, tumor necrosis factor-α and interleukin 6 production and myeloperoxidase activity induced by carrageenan. In conclusion, the results of the present study demonstrate the activity of RI75 in models of inflammatory and neurophatic pain and inflammation. The activity of RI75 is associated with activation of the opioidergic and serotoninergic pathways and reduction of cytokines production and leukocyte recruitment. The results pave the way to further pre-clinical assays to evaluate the toxicological and pharmacokinetic profiles, essential steps aiming the development of new pharmacotherapeutic alternatives.